МОЛЕКУЛЫ АДГЕЗИИ: РОЛЬ В ПРОГНОЗИРОВАНИИ ТЕЧЕНИЯ ЦИРРОЗА ПЕЧЕНИ - А. В. Ягода; П. В. Корой; Г. И. Гилязова; И. С. Мухорамова (SINAPS LLC, 2014)
The blood levels of molecules of immunoglobulins and selectins families in interrelation with the prognosis of liver cirrhosis were studied. The raised risk of death and low survival rate of patients within 1 and 3 years of observation were interconnected with high levels of ICAM-1, VCAM-1, E-selectin and P-selectin in blood. The revealed quantitative values of adhesion molecules which have prognostic importance concerning unfavorable events of liver cirrhosis can be used for estimation of survival rate of patients.